Study of the Effect of Blast Geometry Based on Multiple Linear Regression Analysis on Airblast Value at PT. X - akhmad, Ilham; Revia Oktaviani; Lucia Respati; Tommy Trides; Ardhan ismail (ReTII, 2025)
Airblast is an excessive air pressure wave generated by blasting, which can cause environmental disturbances and structural damage in the vicinity of the mining area. The amount of explosive charge and stemming length were identified as the main variables influencing airblast intensity. The research method employed a quantitative approach, utilizing primary data consisting of blasting geometry, explosive charge amount, stemming length, measurement distance, and airblast measurement results using a Micromate, as well as secondary data in the form of maps and technical information of the study site. Multiple linear regression analysis was used to determine the relationship and contribution of each variable to the Sound Pressure Level (SPL) of airblast. The results indicated that both variables significantly affected airblast magnitude. An increase in the amount of explosive charge tended to raise SPL values, while an increase in stemming length reduced them. Most SPL values were below the SNI 7570:2010 noise level standard, although several instances exceeded the recommended limits, necessitating adjustments to blasting design. In conclusion, airblast control can be optimized by regulating the amount of explosive charge per hole and applying stemming lengths suited to local geological conditions. Recommendations include adjusting the powder factor and using stemming materials with optimal density and length to minimize airblast impact